Extended methods for gene–environment‐wide interaction scans in studies of admixed individuals with varying degrees of relationships. Issue 4 (22nd February 2019) - Chen, Yalei; Adrianto, Indra; Iannuzzi, Michael C.; Garman, Lori; Montgomery, Courtney G.; Rybicki, Benjamin A.; Levin, Albert M.; Li, Jia
Abstract: The etiology of many complex diseases involves both environmental exposures and inherited genetic predisposition as well as interactions between them. Gene–environment‐wide interaction studies (GEWIS) provide a means to identify the interactions between genetic variation and environmental exposures that underlie disease risk. However, current GEWIS methods lack the capability to adjust for the potentially complex correlations in studies with varying degrees of relationships (both known and unknown) among individuals in admixed populations. We developed novel generalized estimating equation (GEE) based methods—GEE‐adaptive and GEE‐joint—to account for phenotypic correlations due to kinship while accounting for covariates, including, measures of genome‐wide ancestry. In simulation studies of admixed individuals, both methods controlled family‐wise error rates, an advantage over the case‐only approach. They demonstrated higher power than traditional case–control methods across a wide range of underlying alternative hypotheses, especially where both marginal and interaction effects were present. We applied the proposed method to conduct a GEWIS of a known sarcoidosis risk factor (insecticide exposure) and risk of sarcoidosis in African Americans and identified two novel loci with suggestive evidence of G × E interaction.